Comparative Study of CD105 and Ki-67 in Adenoid Cystic Carcinoma and Polymorphous Low Grade Adenocarcinoma of the Salivary Glands (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
Background: The intersecting clinicopathological features and histological patterns, including cribriform, tubular and solid patterns of adenoid cystic carcinoma (ACC) and polymorphous low-grade adenocarcinoma (PLGA) may end in a problematic diagnosis .ACC has a worse prognosis than  PLGA making distinction important for therapeutic and prognostic purposes . The Aims of this study were to evaluate the immunohistochemical expression of CD105 and Ki-67 in adenoid cystic carcinoma and polymorphous low grade adeoncarcinoma of the salivary glands and to correlate the immunoexpression of these proteins with the clinicopathological findings.Materials and methodsIn this retrospective study , fifty  of archival formalin fixed paraffin embedded tissue samples of salivary gland malignancies  were used,  twenty five  blocks of  adenoid cystic carcinomas   and twenty five  blocks of  polymorphous low grade adenocarcinoma obtained from the archives of the department of oral pathology / college of dentistry / Baghdad university, Al-Shaheed Ghazi hospital, were included  in our study. Four micrometer sections gained and immunostained using monoclonal antibody against CD105 and Ki-67. The immunoexpression was identified  by the presence of brown stain in the cytoplasm of tumor cell in CD105 and the presence of brown stain in the nucleus  of tumor cell in Ki-67. The proportion of cells that expressed the stain was correlated with the clinicopathological data of the patients.Results: CD105 expression was found positive in 21 cases of ACC and 20cases of PLGA localized in tumor cells. andKi-67 expression was found positive in 24 cases of ACC and 23 casesof PLGA localized in tumor cells.Non- significant  statistical  relation  (P=0.801) was  detected  regarding CD105  expression  in  both  types  of  tumor and non- significant  statistical  relation (P= 0.852) was detected  regarding Ki-67 expression in both types of tumor .Non- significant  statistical  relation  (P= 0.05) was  detected  regarding CD105 and Ki-67 expression  in relation to sex, site and stage in  both  types  of  tumor.Conclusion: Weak expression CD105 and  Ki-67 in ACC and PLGA  might be explained by CD105 and  Ki-67 did  not represent an exclusive factors consequently; other factors might be involved in the proliferation, progression and  metastasis of both tumor types.Key words: Adenoid cystic carcinoma, Polymorphous low grade adenocarcinoma , immunohistochemistry, CD105 and Ki-67.